2019
DOI: 10.3390/jcm8091411
|View full text |Cite
|
Sign up to set email alerts
|

Tachycardiomyopathy in Patients without Underlying Structural Heart Disease

Abstract: Tachycardiomyopathy (TCM) is an underestimated cause of reversible left ventricle dysfunction. The aim of this study was to identify the predictors of recurrence and incidence of major cardiovascular events in TCM patients without underlying structural heart disease (pure TCM). The prospective, observational study enrolled all consecutive pure TCM patients. The diagnosis was suspected in patients admitted for heart failure (HF) with a reduced ejection fraction and concomitant persistent arrhythmia. Pure TCM wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 29 publications
0
14
1
Order By: Relevance
“…Recently, in a prospective observational study, Stronati et al ( 21 ) studied patients admitted for acute HFrEF who had evidence of atrial or ventricular arrhythmias on admission. Among patients diagnosed with TCM, AF (77.6%) and AFL (15%) were the most common underlying arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in a prospective observational study, Stronati et al ( 21 ) studied patients admitted for acute HFrEF who had evidence of atrial or ventricular arrhythmias on admission. Among patients diagnosed with TCM, AF (77.6%) and AFL (15%) were the most common underlying arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, tricuspid regurgitation may serve as a marker of left-sided heart disease and is related to volume overload with possible RV dysfunction, which was also demonstrated in the reduced LVEF group. [ 2 , 22 24 ]…”
Section: Discussionmentioning
confidence: 99%
“…The incidence and prevalence of AF-induced cardiomyopathy is currently unknown, but can reach up to 77% depending on the study population because this cardiomyopathy appears to be under-recognised. [ 2 ] Patients with both AF and heart failure are expected to experience worse outcomes. [ 3 ] Diagnosis arrhythmia-induced cardiomyopathy relies on ruling out other causes of dilated cardiomyopathy, such as coronary artery disease and severe valvular disease, and proving left ventricular (LV) function improvement after restoration of sinus rhythm (SR).…”
mentioning
confidence: 99%
“…In a series of very recent papers [17][18][19][20], the clinical effects of the left ventricle dysfunction were deeply investigated, making our research algorithm suitable for most of these observed and reported clinical symptoms.…”
Section: Conclusion and Final Discussionmentioning
confidence: 99%